The effect of the application of compost and nematicide on the dynamics of microorganism populations, soil phytoparasite nematodes and the root system health in the banana crop (Musa AAA) planted on domes - Araya, María (2014)
The effect of implementing 6 doses of compost plus a control, interacting with the nematicide application or non-application, on the dynamics of the soil microorganisms population (bacteria, fungi and actinomycetes), the phytoparasite nematode populations and the root system health of the banana crop, were evaluated. The results did not show any difference in microorganism populations in relation to the different compost dose or to the nematicide implementation or non implementation. Regarding the biological diversity idexes, in the fungus populations no differences were obtained according to the compost dose, but they were in regard to the nematicide application or non-application, being larger with the richness variable in the first case. The root system health did not differ with the different compost doses, nor with or without nematicide; there were only differences depending on the sampling carried out. Finally, the phytoparasite nematode populations did not show any difference due to the compost dose, except for Pratylenchus. As regards to the nematicide application, all populations were larger in the area where no nematicide was applied.